Modification of Silica Coated on Iron Sand Magnetic Material with Chitosan for Adsorption of Au(III) - Muflikhah Muflikhah; Bambang Rusdiarso; Edy Giri Rachman Putra; Nuryono Nuryono (Indonesian Journal of Chemistry, 2017)
Modification of silica coated on magnetic material iron sand with chitosan for adsorption of Au(III) has been carried out. Magnetic material (MM) from iron sand was separated using an external magnet, washed with water and HF solution 10%. MM–silica–chitosan material (MMSC) was synthesized via sol gel process and the product was characterized with Fourier Transform Infrared (FT-IR) spectrophotometer, X–ray diffractometer, scanning electron microscopy and energy dispersive X–ray, thermogravimetric analysis, and vibration sample magnetometer. Additionally, the effect of pH on the stability of MMSC has also been tested. The adsorption of Au(III) on MMSC was proceeded in a batch system with variation of pH, contact time, and concentration of absorbate. Adsorbent was separated using external magnet and concentration of Au(III) not adsorbed was analyzed using Atomic Absorption Spectrometer. Characterization result indicated that MMSC was successfully synthesized. Adsorption of Au(III) on MMSC followed pseudo second-order kinetic model with the value of adsorption rate constant (k) of 4.10 x 10-3 g mg-1 min-1 and adsorption isotherm fixed with Langmuir model with the adsorption capacity (qmax) of 149.25 mg g-1.